Advanced thermal management for temperature homogenization in high-power lithium-ion battery systems based on prismatic cells - Gepp, M.; Filimon, R.; Koffel, S.; Lorentz, V. R.H.; Marz, M. (IEEE International Symposium on Industrial Electronics, 2015)
In order to extend the lifetime of lithium-ion batteries, an advanced thermal management concept is investigated. In battery modules, different cell temperatures lead to higher efforts in cell balancing and reduce the system's lifetime. Especially when battery systems with phase change material operate outside the phase transition range high temperature gradients can occur that result in different ageing speeds of the cells. The effect of temperature dependent ageing of the battery cells is further investigated. A battery module concept is developed with focus on temperature homogenization by optimization of the module design and material characteristics. The module design combines several approaches including optimized interface pads, thermal storage materials and anisotropic multilayer graphite sheets. Numerical simulations with material and geometrical models are used for the evaluation of the concept with reference models. In addition, a battery cell model is set up, which describes the reversible and irreversible heat generation rate. Using model-order-reduction, the simulations are accelerated by reduction of the calculation time. In order to optimize the material parameters, the simulations are analyzed with design exploration techniques. As a result, the overall temperature differences in the module are minimized and the temperature distribution is homogenized with new developed interface pads. In combination with high thermally conductive synthetic graphite sheets the pads also compensate the insulating behavior of thermal storage material, which is used for temperature peak reduction and to smooth temperature changes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: design optimization; FEM simulation; heat generation; lifetime increase; lithium-ion batteries; model-order-redcution; passive thermal management; temperature homogenization